ASSESSMENT OF THE ROLE OF NUTRITIONAL STATUS AND THE CORRECTION OF MALNUTRITION IN BLOOD CANCER CHILDREN: ANALYSIS OF GLOBAL EXPERIENCE - N. S. Karpenko; N. P. Shen (Вестник анестезиологии и реаниматологии)
The paper analyses the literature, the results of which suggest that there are currently no unified scientifically grounded guidelines for the diagnosis of malnutrition in children with blood cancer. Analysis of global experience demonstrates the need for comprehensive nutritional screening and elaboration of an individualized nutrition support program to enhance the efficiency of treatment.